Psychology professors research production differences in theses and articles in Spain by gender - Olivas-Avila, José Alonso; Musi-Lechuga, Bertha; Guillen-Riquelme, Alejandro; Castro, Ángel (Anales de Psicología / Annals of Psychology, 2012)
The aim of this work is to analyze whether differences exist in the scientific research of the most productive professors in Spanish psychology based on their gender. For this purpose, we analyzed the production of a sample of the 610 most productive professors in the different areas of psychology in articles published in journals of the Journal Citation Reports, by citations of these articles and in doctoral dissertations directed. The results show that the production of males higher than is for women in the indicators analyzed, with variable differences based on psychology areas. The discussion examines the causes of these differences, focusing in the later entry of women to the Spanish university